2015
DOI: 10.11124/jbisrir-2015-2263
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of using non-traditional teaching methods to prepare student health care professionals for the delivery of mental state examination: a systematic review

Abstract: This systematic review study identified teaching strategies utilized in the teaching of mental state examination and their effectiveness. Videotapes was the most widely used and effective approach, that is, until the issue of high cost and ease of maneuver in virtual simulation could be overcome. There were also potential benefits of other teaching, such as reflection and use of standardized patients, and educators could consider these in the teaching of mental state examination. Future research could focus mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Educational interventions including surveys, online modules and didactics were correlated with a marked increase in HCV screening rates within the housestaff practice. Similar educational strategies have been successful at introducing guidelines into practice and leading to behaviour change, but are likely to fail in isolation. HCV screening rates continued to rise as providers received aggregate monthly feedback, a strategy that has been effective at meeting clinical quality indicators in other realms.…”
Section: Discussionmentioning
confidence: 99%
“…Educational interventions including surveys, online modules and didactics were correlated with a marked increase in HCV screening rates within the housestaff practice. Similar educational strategies have been successful at introducing guidelines into practice and leading to behaviour change, but are likely to fail in isolation. HCV screening rates continued to rise as providers received aggregate monthly feedback, a strategy that has been effective at meeting clinical quality indicators in other realms.…”
Section: Discussionmentioning
confidence: 99%
“…Standardized patients (SPs) have been used in medical education for almost 50 years [ 1 ]. Previous literature has demonstrated that training with SPs in medical education is a valuable tool [ 2 ], correlating with a high learners’ satisfaction [ 3 ] and an improvement in learners’ understanding of certain topics and skills [ 4 ]. Training with SPs prepared students to handle a broad range of psychiatric patients, especially those who suffer from alcohol abuse [ 5 ], suicidal tendencies [ 6 ], and patients at the end of their lives [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, case-based e-learning programs and simulated patient (SP) contact might be implemented. Current literature demonstrates that case-based e-learning and especially training with SPs in medical education are valuable tools (Levine and Swartz 2008 ; McNaughton et al 2008 ), correlating with a high learners’ satisfaction (Himmelbauer et al 2018 ; Seitz and Löffler-Stastka 2015 ) and an improvement in learners’ understanding of certain topics and skills (Xie et al 2015 ). The SP might play different roles in various settings, so the student learns sexual health care in different medical fields like internal medicine, obstetrics, or psychiatry.…”
Section: Discussionmentioning
confidence: 99%